Analyzing the Implementation of Total Quality Management Principles in Character Education Programs at Madrasah Ibtidaiyah - Muhammad Syifa' Nurdi; Amala Bilqis Ahmad (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study addresses the limited understanding of how Islamic schools strategically apply Total Quality Management (TQM) principles in character education programs. Specifically, this research investigates the implementation of five core TQM principles: involvement of people, customer focus, process approach, continuous improvement, and human resource management in managing flagship character development initiatives at Madrasah Ibtidaiyah QITA. Employing a qualitative case study approach, data were collected through semi-structured interviews with the principal and teachers, classroom observations, and document analyses of program implementation records. Findings indicate that Madrasah Ibtidaiyah QITA effectively integrates TQM principles through structured daily routines, strong collaboration between teachers and parents, systematic semester-based evaluations, and targeted professional development for educators. The structured implementation of these principles resulted in improved consistency in student character development activities and enhanced program sustainability. This study contributes to existing research by presenting a practical TQM-based model for systematically embedding character education into school culture, which is particularly valuable for Islamic educational institutions. The implementation of TQM principles strengthens the quality and consistency of character education in the madrasah, enhances stakeholder collaboration, and systematically promotes program sustainability. This model can be a reference for other Islamic educational institutions to integrate quality management into effective and sustainable student character development.